2019
DOI: 10.1039/c9ra02221j
|View full text |Cite
|
Sign up to set email alerts
|

A comparative performance analysis of stand-alone, off-grid solar-powered sodium hypochlorite generators

Abstract: Solar-powered electrochemical technologies can be employed to generate valuable chemical commodities on-site. We demonstrate solar-driven production of sodium hypochlorite, a widely employed water disinfection agent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…The second involves supplying, without limits, the NaOCl needed to sterilize the waters produced by the desalination facilities. The cost effectiveness of OSG for NaOCl has been investigated and confirmed by early reports [8][9][10].…”
Section: Introductionmentioning
confidence: 72%
“…The second involves supplying, without limits, the NaOCl needed to sterilize the waters produced by the desalination facilities. The cost effectiveness of OSG for NaOCl has been investigated and confirmed by early reports [8][9][10].…”
Section: Introductionmentioning
confidence: 72%
“…Besides H 2 O 2 , chlorine gas (Cl 2 ), bromine gas (Br 2 ) and sodium hydroxide (NaOH) are usually advocated as interesting anodic products. 8,54 More recently, Palmer et al showed that also uorine, iodine, methane decomposition (to carbon), potassium permanganate, sodium bromate, sodium chlorate and sodium persulfate production should be considered. 46 They based this on the calculation of the net value of the chemicals per unit of energy input.…”
Section: àmentioning
confidence: 99%
“…A first laboratory prototype with seven cells achieved a direct sunlight conversion efficiency of 36.4% in 2016. 9,10 A pilot site is installed since 2017 at the rooftop of EPFL, Switzerland (Figure 1A) to validate the robustness of the module architecture and tracking mechanism. 10 In 2019, a 0.1-m 2 pre-series module was characterized with a 29.0% efficiency at Concentrator Standard Test Conditions (CSTC, as defined in IEC 62670-1).…”
Section: Insolight's Planar Micro-tracking Module With Diffuse Light Harvestingmentioning
confidence: 99%